Redesigning the course: “Dynamisk biokemi” for B.Sc. in Pharmacy - Byriel Walls, Anne (Improving University Science Teaching and Learning, 2023)
The aim of this project is to redesign and optimize the course ”Dynamisk biokemi” for students taking a B.Sc. in Pharmacy so that the teaching and learning activities (TLAs) better support deeper learning, i.e. enforce understanding rather than memory.